Beryllium ionisation by ion impact. (July 2015) - López, S D; Randazzo, J M; Picca, R Della; Colavecchia, F D
Synopsis: We study ionization of Beryllium atoms by ion impact with continuum distorted waves models. We calculate cross sections in the intermediate to high energy regime for state resolved and total ionization.